Activation of the sirtuin silent information regulator 1 pathway inhibits pathological myocardial remodeling - Wang, Youheng; Zhao, Rusheng; Wu, Chengyan; Liang, Xuefei; He, Lei; Wang, Libo; Wang, Xuehui (Frontiers in Pharmacology, 2023)
Myocardial remodeling refers to structural and functional disorders of the heart caused by molecular biological changes in the cardiac myocytes in response to neurological and humoral factors. A variety of heart diseases, such as hypertension, coronary artery disease, arrhythmia, and valvular heart disease, can cause myocardial remodeling and eventually lead to heart failure. Therefore, counteracting myocardial remodeling is essential for the prevention and treatment of heart failure. Sirt1 is a nicotinamide adenine dinucleotide+-dependent deacetylase that plays a wide range of roles in transcriptional regulation, energy metabolism regulation, cell survival, DNA repair, inflammation, and circadian regulation. It positively or negatively regulates myocardial remodeling by participating in oxidative stress, apoptosis, autophagy, inflammation, and other processes. Taking into account the close relationship between myocardial remodeling and heart failure and the involvement of SIRT1 in the development of the former, the role of SIRT1 in the prevention of heart failure via inhibition of myocardial remodeling has received considerable attention. Recently, multiple studies have been conducted to provide a better understanding of how SIRT1 regulates these phenomena. This review presents the progress of research involving SIRT1 pathway involvement in the pathophysiological mechanisms of myocardial remodeling and heart failure.